Use of Preoperative 3D Virtual Planning and 3D-Printed Patient-Specific Guides to Facilitate a Single-Stage Cranial Closing Wedge Ostectomy and Tibial Plateau Leveling Osteotomy Procedure to Address Proximal Tibial Deformity, an Excessive Tibial Plateau Angle, and Cranial Cruciate Ligament Insufficiency in a Dog - Christina C. De Armond; Daniel D. Lewis; Sarah Townsend (Case Reports in Veterinary Medicine)
A 9-month-old mixed-breed dog was presented for bilateral proximal tibial deformity resulting in an excessive tibial plateau angle and cranial cruciate ligament insufficiency. Initial surgical management of the right pelvic limb was done by performing a cranial closing wedge ostectomy. Inadequate leveling of the plateau resulted in a postliminal meniscal tear which was addressed during a revision tibial plateau leveling osteotomy. The left pelvic limb was managed in a single-session surgery using three-dimensional (3D) virtual surgical planning and custom 3D-printed surgical guides to perform a combined cranial closing wedge ostectomy and tibial plateau leveling osteotomy. Postoperative 3D analysis of the left tibia revealed the accuracy of the surgical result within 2° of the virtual surgical plan. The dog developed a transient grade II/IV left medial patellar luxation following surgery but ultimately attained a full functional recovery and was actively engaged in competitive agility work 46 months following surgery on the left pelvic limb.